EARLY VERSUS DELAYED LAPAROSCOPIC CHOLECYSTECTOMY FOR ACUTE CHOLECYSTITIS - Khalid, Sadaf; Iqbal, Zahid; Bhatti, Afsar Ali (Journal of Ayub Medical College Abbottabad, 2017)
Background: Laparoscopic cholecystectomy is considered the gold standard for the management of acute cholecystitis but controversy surrounds the timings of the surgery. Studies are available favouring both early and delayed laparoscopic cholecystectomy. The objective of this study was to compare early versus delayed laparoscopic cholecystectomy for acute cholecystitis. Methods: This quasi-experimental study included 180 patients irrespective of their age and sex presented at department of Surgery, Lahore General Hospital between January to December 2014 with a diagnosis of acute cholecystitis were assigned randomly to early laparoscopic cholecystectomy within 24 h of admission or to initial conservative treatment followed by delayed laparoscopic cholecystectomy, 6-12 weeks later. Results: The mean operating time was 64.32 min vs. 58.24 min in the delayed group, conversion rate (early 15.5% vs. delayed 14.4%). The mean postoperative hospital stay was 1.67 days in the earlier group and 4.38 days in the delayed group. Overall mortality was zero. Conclusion: Early laparoscopic cholecystectomy for acute cholecystitis is safe, offering economic benefit of much shorter hospital stay and quick recovery. Keywords: Acute cholecystitis; Laparoscopic cholecystectomy; Early cholecystectomy